2012
DOI: 10.17221/29/2012-jfs
|View full text |Cite
|
Sign up to set email alerts
|

Effects of roads on understory plant communities in a broadleaved forest in Hyrcanian zone

Abstract: This study was conducted to assess the effect of forest road as a corridor on local biodiversity. For this purpose, 10 segments in a 10 year-old road were selected in Neka-Zalemrood forest in Hyrcanian zone. At each of the segments, we established two 100-m transects perpendicular to the road centre line, within which we sampled three macroplots of an area 400 m<sup>2</sup>. In each macroplot, nine quadrant microplots 2 &times; 2 m in size were set up for regenerated tree species and herbaceous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…Soil can be a factor in increasing the frequency of herbaceous cover on the side of the road. The reason for the presence and abundance of many herbaceous species is due to greater access to light or soil nitrogen, which affects the growth, composition and diversity of species (Karim and Mallik 2008, Avon et al 2010, Lotfalian et al 2012, Boston 2016, Deljouei et al 2018, Fallahchai et al 2018, Lisboa et al 2022). Soil is a parameter that is greatly affected by road construction and many of its characteristics can be changed.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Soil can be a factor in increasing the frequency of herbaceous cover on the side of the road. The reason for the presence and abundance of many herbaceous species is due to greater access to light or soil nitrogen, which affects the growth, composition and diversity of species (Karim and Mallik 2008, Avon et al 2010, Lotfalian et al 2012, Boston 2016, Deljouei et al 2018, Fallahchai et al 2018, Lisboa et al 2022). Soil is a parameter that is greatly affected by road construction and many of its characteristics can be changed.…”
Section: Discussionmentioning
confidence: 99%
“…The available TP, pH, SM, N, P, K and Ca parameters had the greatest effect on diversity and richness. Lotfalian et al (2012) showed that soil organic carbon, silt, moisture, lime, Ca and clay have no effect on biodiversity indicators. The results of the study by Karim and Mallik (2008) showed that the lowest amount of moisture and organic matter and the highest BD are seen on the shoulders of the roads.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations